2021
DOI: 10.1186/s12889-021-12046-3
|View full text |Cite
|
Sign up to set email alerts
|

Advance directives and end-of-life care preferences among adults in Wuhan, China: a cross-sectional study

Abstract: Background Little is known about advance directives (ADs) and end-of-life (EOL) care preferences among the general population in Mainland China. This study aimed to describe knowledge and attitudes of ADs and EOL care preferences, and to explore factors related to preferences for ADs among Chinese adults. Methods The sample included 1114 adult participants in Wuhan, Mainland China. A brief message including the link to the online survey was sent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Domestic studies also indicated that older adults were not evasive about dying [ [53] , [54] , [55] ]. However, domestic studies also showed the necessity of death education [ 29 , [56] , [57] , [58] , [59] ]. Participants in this study were purposefully selected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Domestic studies also indicated that older adults were not evasive about dying [ [53] , [54] , [55] ]. However, domestic studies also showed the necessity of death education [ 29 , [56] , [57] , [58] , [59] ]. Participants in this study were purposefully selected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, The study indicated that relatively few aged citizens completed the forms due to lacing Internet technology abilities as the ‘Five Wishes’ forms were online and digital [ 24 ]. Furthermore, Chinese scholars conducted cross-sectional studies on the recognition, acceptance, knowledge, attitude and practice (KAP) of ADs using self-designed questionnaires among terminally ill patients, older adults and health professionals [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Overall, the recognition, acceptance, knowledge and KAP of ADs among the population improved over time [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In terms of the variable of physical health, the results from a cross-sectional study reported that patients with high comorbid conditions were more likely to complete an advance directive among 456 older nursing home residents. 16 Zhu et al 15 conducted a mixed-method study among 523 community older adults and the results showed that poor health condition was more preference toward advance care planning. Moreover, Gallagher et al 12 found that people with experience working in health or social care are likely to have increased advance care planning engagement.…”
Section: Individual Layermentioning
confidence: 99%